Romanization of Spain : socio-political aspect (IV). Romanization during the Early Empire : conclusion I - Tsirkim, Ju B. (Espacio Tiempo y Forma. Serie II, Historia Antigua, 1996)
The Flavian reforms had put an end to the purely legal Romanization of Spain but the depth and intensity of the process seem to have varied in different regions of the country. Like in the late Republican times, in the first and second centuries A.D. Spain had three zones of Romanization - a wholly (or almost wholly) Romanized zone, a Romanizing zone and a non- Romanized region but unlike the previous period the boundaries of them were absolutely different. The former covered practically the whole of Baetics and East Tarraconensis (except the Balearic Islands).